Use of Artificial Intelligence in rheumatoid arthtitis - Kawa, Zuzanna; Kasprzak, Maria; Jędrzejewska, Aleksandra; Jureczko, Aleksandra; Kleczaj, Klaudia; Levadna, Valentyna; Osiński, Damian; Jaworowska, Julia; Kanarszczuk, Julia; Babiarz, Gabriela (Quality in Sport, 2025)
Early diagnosis of rheumatoid arthritis (RA) is essential in preventing irreversible joint damage, disease progression, reducing symptoms, and improving long-term outcomes for patients. Artificial intelligence (AI) including machine learning (ML) and deep learning (DL) have the potential of helping medical professionals in detecting RA at an early stage and therefore helping in disease management and timely intervention. However, more research is required to confirm dependabillity of AI in RA. Despite the promising results achieved by AI models they are not fully ready to be used in clinical practice. Future investigations are required to create reliable algorithms.